Time-Limits for the Performance of Obligations and Legal Effects of Their Extinction - Driukas, Artūras (Teisė, 2018)
Quite a few mistakes still occur in the interpretation and application of legal rules which regulate time-limits in law generally and time-limits for the performance of obligations specifically. The detailed analysis of time-limits for the performance of obligations in jurisprudence is lacking. This article examines the meaning of the time-limits for the performance of obligations, their kinds, the ways of defining these time-limits and legal effects of their extinction. Also, it analyses the parties‘ choices as regards the remedies in the case of breaches of obligations with a term and, finally, the meaning of additional time-limits and the period of grace. The analysis is extensively supported by the case-law which assists in the disclosure of the issues related to the time-limits for the performance of obligations.
Keywords: none